THE RADIO BLOG AS A DIDACTIC PROTOTYPE OF MULTILITERACIES - Cunha, Regiane; Ribeiro, Edinelza (Revista Gênero e Interdisciplinaridade, 2026)
New Information and Communication Technologies (ICTs) dictate a new scenario for school education. Many are the expectations for learning through these new tools involving the use of digital media and technological advances in general, something that has become quite present in people’s lives, especially adolescents. Therefore, it is necessary to consider the paradigm shift from the perspective of teaching today, in the face of so many changes and technological advances. This research focuses on: The Radioblog as a Didactic Prototype for Multiliteracies. The study sought to discuss perceptions and strategies for using the Radioblog as a didactic prototype for Multiliteracies. It is a didactic-methodological strategy that understands that language practices and the production of meaning are socio-historically situated (BAKHTIN, 2003). This research adopted a bibliographic approach with qualitative research, as described by Minayo (2004), using the Didactic Prototype for teaching Portuguese as well as other areas of knowledge. In light of the research results, it has become essential to rethink teaching practices in schools, to understand the use of didactic prototypes in Portuguese language classes as well as in other subject areas, and how this tool can assist teachers in their classroom practice.